Recovery of Agricultural Odors and Odorous Compounds from Polyvinyl Fluoride Film Bags - Parker, David B.; Perschbacher-Buser, Zena L.; Cole, N. Andy; Koziel, Jacek A. (Sensors (Basel, Switzerland), 2010)
Accurate sampling methods are necessary when quantifying odor and volatile organic compound emissions at agricultural facilities. The commonly accepted methodology in the U.S. has been to collect odor samples in polyvinyl fluoride bags (PVF, brand name Tedlar®) and, subsequently, analyze with human panelists using dynamic triangular forced-choice olfactometry. The purpose of this research was to simultaneously quantify and compare recoveries of odor and odorous compounds from both commercial and homemade PVF sampling bags. A standard gas mixture consisting of p-cresol (40 µg m−3) and seven volatile fatty acids: acetic (2,311 µg m−3), propionic (15,800 µg m−3), isobutyric (1,686 µg m−3), butyric (1,049 µg m−3), isovaleric (1,236 µg m−3), valeric (643 µg m−3), and hexanoic (2,158 µg m−3) was placed in the PVF bags at times of 1 h, 1 d, 2 d, 3 d, and 7 d prior to compound and odor concentration analyses. Compound concentrations were quantified using sorbent tubes and gas chromatography/mass spectrometry. Odor concentration, intensity, and hedonic tone were measured using a panel of trained human subjects. Compound recoveries ranged from 2 to 40% after 1 h and 0 to 14% after 7 d. Between 1 h and 7 d, odor concentrations increased by 45% in commercial bags, and decreased by 39% in homemade bags. Minimal changes were observed in intensity and hedonic tone over the same time period. These results suggest that PVF bags can bias individual compound concentrations and odor as measured by dynamic triangular forced-choice olfactometry.